Los órganos colegiados: impacto en la gestión de la administración pùblica local - Mèndez Salas, Lucia del Carmen (2018)
The present investigation, on the Organization and Functioning of the Collegiate Bodies and their impact on the efficiency, quality and transparency of public management, begins with the study of Supreme Decree N ° 006-67-SC, which determines the separation of the administrative activity, of the civil control and consolidated with the Law 27444, that establishes the dogmatic and normative autonomy of the administrative procedure of the civil process. The subject of Public Administration, Administrative Law, the Law of the Organization and the Institute of Organic Dissension is also studied to locate with precision the legal nature of the collegiate bodies. The 5 phases or stages are studied, which determine the birth of the collegial act: 1) Appointment; 2) Call; 3) Quorum; 4) Deliberation and 5) Voting, in Law 27444, TUO: DS N ° 006-2017-JUS. Finally, the Collegiate Bodies promote a more democratic and transparent public management, demanding that its members be fully aware of what they are going to decide, when they determine the compulsory nature of the vote, within the structure of the collegiate bodies, protecting the legality, a more participatory and transparent public management, as well as the Rights of the Managers. The conclusions have arisen, use of the inductive - deductive methods; analytical, synthetic and legal. The application of dogmatic and regulations of the collegiate bodies in the Municipality of Carabamba, within acceptable margins.